Long-lasting pure topographical disorientation due to heading disorientation following left retrosplenial infarction: A report of two cases - Kawakami, Nobuko; Okada, Yuri; Morihara, Keisuke; Katsuse, Kazuto; Kakinuma, Kazuo; Matsubara, Shiho; Kanno, Shigenori; Suzuki, Kyoko (Brain and cognition, 2024)
•We report 2 persisting topographical disorientation (TD) cases post stroke.•The lesion in the retrosplenial region was left-side, atypical for causing TD.•No other deficits affecting TD were detected, implying pure heading disorientation.•Impairments in reconstructing and integrating egocentric & allocentric inferences.•Left retrosplenial region can cause pure long-lasting heading disorientation. Topographical disorientation is linked to lesions in the right hemisphere and typically resolves within a few months post-stroke. Persistent topographical disorientation is uncommon and frequently accompanied by impairments in visual memory, complicating the analysis of the underlying mechanisms. Herein, we report two cases of sustained pure topographical disorientation following cerebral hemorrhages in the left retrosplenial region. The patients exhibited disorientation in both familiar and unfamiliar settings, attributable to heading disorientation, a deficit in determining the directional relationship between one’s current position and a target location or external frames. The patients struggled with reconstructing large-scale spatial frameworks and integrating new egocentric and allocentric perspectives upon changes in body orientation. There were no landmark agnosia, egocentric disorientation, or anterograde disorientation. Although mild verbal memory deficits were observed, no other cognitive impairments, including visual memory deficits, were detected. Our findings imply that lesions confined to the left retrosplenial region can induce enduring heading disorientation and suggest a significant role for this area in processing and integrating spatial information necessary for large-scale navigation. Clarifying the features of topographical disorientation will significantly impact the therapeutic approaches, enhancing the quality of life for affected patients by restoring their independence and mobility.